The three musketeers ebook - Dumas, Alexandre (d'Artagnan Romance, 2012)
The Three Musketeers follows the young d'Artagnan in his quest to become a musketeer. He befriends the three musketeers Athos, Porthos and Aramis, whose motto is "all for one, one for all." The novel is the first in Dumas' d'Artagnan Romances trilogy.